EZ-Umberbike / Nurshahira Ruslan - Ruslan, Nurshahira (2020)
Rainy day becomes a problem for some people especially the one who use a bicycle as a main transport. So, our EZ-UMBERBIKE will helps them to overcome this problem as it can fully protect the users body, easy to be install and affordable. It also comes with side mirror for safety features. The various colour and pattern of EZ-UMBERBIKE will make it suitable for many people; either young or old man. This bike umbrella comes with special features like sturdy, windproof, waterproof, safety and anti-theft features as it is created using double canopy design for wind protection, 3 digit password padlock for anti-theft features and high quality materials for long lasting effect. The double canopy technology are applied to this bike umbrella to prevent the accumulation of pressure at the supporting structure and thus to prevent the damage of this structure by a strong wind. A special anti-theft features that created by applying the 3 digit password padlock for both umbrella stand and side mirror will becomes a special features that cannot be found at other bike umbrella. EZ-UMBERBIKE are made up of high quality polyester pongee fabric, sturdy tempered spring rod, light-weight aluminium stretcher, sturdy umbrella stand and small side mirror with 3 digit padlock. We will introduce our bike umbrella to the public and will make it trending in Malaysia so that we can increase our market size in future. The EZ-UMBERBIKE has features and functions that cannot be found in current’s bike umbrella, thus, it will provide a competitive advantages over the other recognised competitors.